Calibration of Measuring Channels for the Analysis of the High-Power Microwave Impulse Parameters; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Galchenko V. G. Valery Grigorievich (2016, 2016)
Title screen